Are we doing enough? Nigerian Female Undergraduates’ Knowledge and Use of Female Condom. - Oscar, Yomi Akindele -; Ogunsanwo, Mojisola; Adesina, Sekinat; Ogayemi, Mercy Omowunmi (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
Female undergraduates’ population in Nigeria though heterogeneous, is dominated by young people who have high sexual mobility and engage in sporadic and unstable sexual intercourse which tends to expose them to health compromising behaviours such as non-usage or inconsistent use of female condom. This study interrogated female undergraduates’ knowledge and use of female condom in Nigeria. The descriptive research design was adopted for the study. The study’s participants were five hundred and thirty-one female undergraduates drawn from six faculties in a Nigerian university. The Female Condom Knowledge and Use Scale (FCKUS), a 12-item questionnaire developed by the researchers with attendant psychometric properties ensured, was used for data collection. Results indicated that 31.4% of female undergraduates have seen a female condom before while 68.6% have not. The sources of knowledge about female condom were mostly from Peer group/friends (32%) and the least was from parents (4%). There was also a significant difference between New–intakes and Stalites female undergraduates’ knowledge and use of female condoms. Also, there was a significant difference in the knowledge and use of female condom by female undergraduates below and those above 20 years old. However, there was no significant difference in the knowledge and use of female condoms of participants in Science faculty and those in Non-science faculties. The study concluded that we are not doing enough advocacy on female condom as a nation. It was recommended that more advocacy is needed, while free distribution of female condoms to female undergraduates periodically by Government Agencies/ Health Institutions and NGOs should be explored just like they do for male condoms. Keywords: Female Condom; Knowledge; Use; Undergraduates.